When war ends building peace in divided communities - Francis, David J., 1965- (Ashgate Pub., 2012)
This volume critically examines what happens when war formally ends, the difficult and complex challenges and opportunities for winning the peace and reconciling divided communities. By reviewing a case study of the West African state of Sierra Leone, potential lessons for other parts of the world can be gained. Sierra Leone has emerged as a 'successful' model of liberal peacebuilding that is now popularly advertised and promoted by the international community as a powerful example of a country that they finally got right.